Spherical-like iron phosphate as well as preparation method and application thereof
Through two stages of hydrothermal reaction and spray drying + sintering, the problem of insufficient tap density and crystallinity in iron phosphate synthesis was solved, and a high-performance spherical iron phosphate was prepared to prepare high-efficiency lithium iron phosphate materials, realizing the High specific capacity and low resistance effects.
Patent Information
- Application Number
- CN202411353108.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing iron phosphate synthesis process has problems such as low tap density, low reaction activity, low crystallinity and serious agglomeration, which affects the comprehensive electrical performance of lithium iron phosphate.
The two-stage hydrothermal reaction method and spray drying + sintering method are used to control the molar ratio of iron element to phosphorus element and the addition ratio of ammonium dihydrogen phosphate, and the specific surface area and crystallinity of iron phosphate are improved through hydrothermal reaction, thereby reducing agglomeration. Form spherical iron phosphate.
The prepared iron phosphate has high tap density, narrow particle size distribution, high specific surface area and high crystallinity. As a precursor, lithium iron phosphate materials with high compaction, low sintering temperature, low powder resistance and high specific capacity can be prepared.
Smart Images

Figure CN119160865A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferric phosphate preparation, and in particular to quasi-spherical ferric phosphate and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Olivine-structured lithium iron phosphate is one of the cathode materials used in power lithium-ion batteries. Lithium iron phosphate has become one of the most promising cathode materials in the lithium-ion battery industry due to its advantages such as high safety, long cycle life, environmental friendliness and low cost. Lithium iron phosphate prepared with iron phosphate as the iron source precursor, lithium source compounds and added components shows high electrochemical activity and tap density. As a precursor of lithium iron phosphate, iron phosphate has the advantages of non-toxicity, low cost and stable structure. Its physical and chemical properties determine the comprehensive performance of the final product lithium iron phosphate to a certain extent. Therefore, it is necessary to prepare an iron phosphate material with good performance.
[0004] At present, there are two main types of iron phosphate synthesis processes commonly used. One is the sodium co-precipitation process using ferrous sulfate, phosphoric acid, and liquid alkali as raw materials, and the other is the ammonium co-precipitation process using ferrous sulfate and ammonium dihydrogen phosphate as raw materials. The iron phosphate prepared by both processes has problems such as low tap density, low reaction activity when used as a precursor, low crystallinity, severe agglomeration, and too wide particle size distribution. The patent with publication number CN115231539A proposes a wet process for preparing iron phosphate, using ferric chloride and ammonium dihydrogen phosphate as raw materials to prepare iron phosphate, which improves the problem of needing to adjust pH and control reaction speed in the traditional wet process, but still does not improve the key characteristics of iron phosphate that affect the synthesis of lithium iron phosphate.
[0005] Therefore, how to provide a method for preparing iron phosphate to reduce the agglomeration of iron phosphate, increase the specific surface area of iron phosphate to make it have higher reactivity, and improve the crystallinity to improve the comprehensive electrical properties of the finished iron phosphate is an urgent problem to be solved. Summary of the invention
[0006] In view of this, the present invention provides a quasi-spherical iron phosphate and a preparation method and application thereof. The iron phosphate obtained by the preparation method of the present invention has a quasi-spherical morphology, high tap density, narrow particle size distribution, high specific surface area, high crystallinity, and no serious agglomeration. The lithium iron phosphate material prepared using the iron phosphate as a precursor can achieve the effects of high compaction, low sintering temperature, low powder resistance and high specific capacity.
[0007] In a first aspect, the present invention provides a method for preparing quasi-spherical iron phosphate, comprising the following steps:
[0008] S1, mixing ferric sulfate and phosphoric acid in water and performing a hydrothermal reaction; controlling the molar ratio of the iron element to the phosphorus element to be greater than 1;
[0009] S2, after the reaction in step S1 is completed, adding ammonium dihydrogen phosphate so that the total molar amount of ammonium dihydrogen phosphate and phosphoric acid is not less than the molar amount of the iron element, and then performing a hydrothermal reaction;
[0010] S3. After the reaction in step S2 is completed, washing, filtering, spray drying and sintering are performed in sequence to obtain quasi-spherical iron phosphate.
[0011] Preferably, in step S1, the molar ratio of iron element to phosphorus element is 1:(0.52-0.6); the molar ratio of diammonium phosphate in step S2 to phosphoric acid in step S1 is 1:(0.8-1.1).
[0012] Preferably, the ferric sulfate in step S1 is obtained by oxidizing ferrous sulfate with an oxidant.
[0013] Furthermore, the oxidant is selected from one or more of hydrogen peroxide, ozone, oxygen, sodium peroxide, potassium persulfate or ammonium persulfate.
[0014] Furthermore, the ferrous sulfate is obtained by removing impurities from the titanium dioxide byproduct ferrous sulfate with an impurity remover; the impurity remover is selected from one or more of Na2S, (NH4)2S or BaS.
[0015] Preferably, the reaction temperature of the hydrothermal reaction of step S1 and step S2 is 140-200° C., and the reaction time is 1-5 h.
[0016] Preferably, the hydrothermal reaction in step S1 further contains a surfactant, and the added amount of the surfactant is 0.03-0.06 wt %.
[0017] Furthermore, the surfactant is selected from one or more of sodium dodecylbenzene sulfonate, dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate or sodium stearate.
[0018] Preferably, the feed rate of the spray drying is 3-8 L / h, the inlet temperature is 220-250°C, and the outlet temperature is 110-120°C.
[0019] Preferably, the sintering step of step S3 is specifically as follows: heating to 450-550° C. at a heating rate of 3-8° C. / min, and sintering at the temperature for 2-6 hours.
[0020] In a second aspect, the present invention provides quasi-spherical iron phosphate prepared by the above preparation method.
[0021] In a third aspect, the present invention provides an application of the quasi-spherical iron phosphate, wherein the application is to use the quasi-spherical iron phosphate to prepare a lithium iron phosphate positive electrode material.
[0022] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0023] (1) The present invention adopts a two-stage hydrothermal reaction (high-pressure liquid phase method) to prepare dihydrated ferric phosphate material. The hydrothermal reaction itself can make the raw materials dispersed more evenly during the precipitation process and the precipitation reaction temperature higher, thereby improving the purity of the product ferric phosphate and the precipitation efficiency; and the present invention adds two different phosphorus sources (phosphoric acid and diammonium dihydrogen phosphate) in the two-stage hydrothermal reaction respectively, so that the subsequent precipitation can be wrapped and precipitated on the existing ferric phosphate crystals, and more mesoporous voids can be retained on the basis of further improving the compactness of the crystallized product. The macroscopic manifestation is an increase in specific surface area, which is beneficial to the improvement of the reaction activity of the final product anhydrous ferric phosphate.
[0024] (2) The present invention uses a spray drying + sintering method to remove the crystal water in the dihydrated iron phosphate. Spray drying can further shrink the larger voids inside the precipitated product to increase the tap density. At the same time, the morphology of the obtained spherical aggregated iron phosphate, i.e., quasi-spherical iron phosphate, is conducive to the improvement of the tap density. It can also shorten the time required for subsequent sintering to remove the crystal water, so that the anhydrous iron phosphate after sintering has higher crystallinity.
[0025] (3) The iron phosphate material prepared by the present invention has the characteristics of high tap density, narrow particle size distribution, high specific surface area, high crystallinity, and no serious agglomeration. The lithium iron phosphate material prepared using the iron phosphate as a precursor can achieve the effects of high compaction, low sintering temperature, low powder resistance and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is a scanning electron microscope image of the quasi-spherical anhydrous ferric phosphate material prepared in Example 1 of the present invention, with a magnification of 2k;
[0028] Figure 2 This is a scanning electron microscope image of the quasi-spherical anhydrous ferric phosphate material prepared in Example 1 of the present invention, with a magnification of 100k;
[0029] Figure 3This is a particle size distribution diagram of the quasi-spherical anhydrous ferric phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] In a first aspect, the present invention provides a method for preparing quasi-spherical iron phosphate, comprising the following steps:
[0032] S1, mixing ferric sulfate and phosphoric acid in water and performing a hydrothermal reaction; controlling the molar ratio of the iron element to the phosphorus element to be greater than 1;
[0033] S2. After the reaction in step S1 is completed, diammonium dihydrogen phosphate is added so that the total molar amount of diammonium dihydrogen phosphate and phosphoric acid is not less than the molar amount of the iron element, and then a hydrothermal reaction is carried out;
[0034] S3. After the reaction in step S2 is completed, washing, filtering, spray drying and sintering are performed in sequence to obtain quasi-spherical iron phosphate.
[0035] The present invention adopts a two-stage hydrothermal reaction (high-pressure liquid phase method) to prepare a dihydrated iron phosphate material. The hydrothermal reaction can make the raw materials dispersed more evenly during the precipitation process, and the reaction temperature of the precipitation is higher, thereby improving the purity and precipitation efficiency of the product iron phosphate. At the same time, the present invention adds two different phosphorus sources in two stages of hydrothermal reactions respectively, in order to adjust the concentration of the raw materials involved in the reaction, so that the growth rate of the precipitated crystals is slightly higher than the nucleation rate, and the compactness of the crystallized product is improved. Phosphoric acid is first added to maintain the pH of the precipitation system at about 2 to 3, and spherical iron phosphate precipitation is easily generated at a lower pH; then ammonium dihydrogen phosphate is added for a two-stage reaction, which can increase the pH of the system to a certain extent, accelerate the precipitation rate, and enable subsequent precipitation to be wrapped and precipitated on the existing spherical iron phosphate crystals, and can retain more mesoporous voids on the basis of further improving the compactness of the crystallized product, and the macroscopic performance is an increase in specific surface area, thereby improving the reaction activity of the final product anhydrous iron phosphate. Because the synthesis of lithium iron phosphate follows the core shrinkage reaction kinetic model, the molten lithium salt will form a lithium iron phosphate product layer on the surface of the iron phosphate. As the reaction proceeds, the two-phase reaction interface of iron phosphate (core phase) and lithium iron phosphate (shell phase) moves inward, and the core phase gradually shrinks until it is completely converted into lithium iron phosphate. Therefore, the presence of mesoporous voids can promote the penetration and diffusion of reactants, increase the rate of the shrinkage reaction, and increase the reaction activity.
[0036] After two-stage hydrothermal reaction, dihydrated ferric phosphate can be prepared. The present invention uses a spray drying + sintering method to remove the crystal water in the dihydrated ferric phosphate. Spray drying can further shrink the larger voids inside the precipitated product to increase the tap density. At the same time, the morphology of the obtained spherical aggregated ferric phosphate, i.e., the quasi-spherical ferric phosphate, is conducive to the improvement of the tap density. It can also shorten the time required for subsequent sintering to remove the crystal water, so that the anhydrous ferric phosphate after sintering has higher crystallinity.
[0037] In step S1 of the present invention, the molar ratio of iron element to phosphorus element is preferably 1:(0.52-0.6), and the molar ratio of ammonium dihydrogen phosphate in step S2 to phosphoric acid in step S1 is preferably 1:(0.8-1.1), and most preferably 1: 1. In the present invention, the phosphorus source is divided into two parts, which are added in two stages and react with ferric sulfate to generate dihydrated ferric phosphate.
[0038] In the present invention, the ferrous sulfate described in step S1 is obtained by oxidizing ferrous sulfate with an oxidant, and the oxidant is selected from one or more of hydrogen peroxide, ozone, oxygen, sodium peroxide, potassium persulfate or ammonium persulfate. The present invention does not impose any special restrictions on the manner in which ferrous sulfate and phosphoric acid are mixed in water, and a mixing manner commonly used in the art can be adopted. The present invention preferably adds phosphoric acid to an aqueous solution of ferrous sulfate for stirring and mixing; the present invention does not impose any special restrictions on the concentration of the aqueous solution of ferrous sulfate, and a concentration of an aqueous solution of ferrous sulfate commonly used in hydrothermal reactions in the art can be adopted. The present invention preferably is Fe 3+ The concentration is 0.5~1mol / L.
[0039] In the present invention, the ferrous sulfate is obtained by removing impurities from the titanium dioxide byproduct ferrous sulfate with an impurity remover; the impurity remover is selected from one or more of Na2S, (NH4)2S or BaS, which can remove copper ion impurities and other metal ion impurities that can generate sulfides. Using the titanium dioxide byproduct ferrous sulfate as the raw material source of ferrous sulfate can greatly reduce the preparation cost. The present invention does not impose any special restrictions on the impurity removal process, and the impurity removal process of the titanium dioxide byproduct ferrous sulfate commonly used by those skilled in the art can be used.
[0040] In the present invention, the reaction temperature of the hydrothermal reaction of step S1 and step S2 is 140-200° C., more preferably 140-160° C.; the reaction time is 1-5 h; more preferably 1-2 h.
[0041] In the present invention, the hydrothermal reaction of step S1 also contains a surfactant, and the addition amount of the surfactant is 0.03-0.06wt%, that is, the mass fraction of the mass of sodium dodecylbenzene sulfonate to the total mass of sodium dodecylbenzene sulfonate, phosphoric acid, ferric sulfate and water is 0.03-0.06wt%. The presence of the surfactant can regulate the morphology of iron phosphate and promote the formation of cluster-like spherical iron phosphate precipitation. In the present invention, the surfactant is preferably an anionic surfactant, which can be selected from one or more of sodium dodecylbenzene sulfonate, dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate or sodium stearate.
[0042] The present invention does not impose any special restrictions on the washing and filtering steps in step S3, and the washing and filtering steps commonly used in the art can be used. After the filtration is completed, the filter cake is retained, and then water is added to form a slurry for use in the subsequent spray drying process.
[0043] In the present invention, the feed rate of the spray drying is 3-8 L / h, the inlet temperature is 220-250° C., and the outlet temperature is 110-120° C. The present invention does not impose any special restrictions on the specific steps and equipment of the spray drying.
[0044] In the present invention, the sintering step of step S3 is specifically as follows: heating to 450-550° C. at a heating rate of 3-8° C. / min, and sintering at the temperature for 2-6 hours.
[0045] The present invention also provides a quasi-spherical iron phosphate prepared by the above preparation method, wherein the obtained quasi-spherical iron phosphate has a D50 particle size of 8 to 9 μm and a specific surface area of 17.5 m 2 / g or above, tap density is 0.8g / cm 3 above.
[0046] The present invention also provides an application of the quasi-spherical iron phosphate, wherein the quasi-spherical iron phosphate is used to prepare a lithium iron phosphate positive electrode material. The present invention does not impose any particular restrictions on the method for preparing lithium iron phosphate using iron phosphate, and a commonly used preparation method in the art can be used.
[0047] The technical solution of the present invention is further described below in conjunction with specific embodiments. The "room temperature" mentioned below refers to 25±3°C.
[0048] In the following examples, the preparation process of the ferrous sulfate solution is as follows: deionized water is added to the ferrous sulfate byproduct of titanium dioxide to prepare a crude ferrous sulfate solution, and then a sufficient amount of Na2S is added thereto, and the mixture is stirred at a speed of 30 r / min for 25 min on a magnetic stirrer at room temperature. After the stirring is completed, the mixture is allowed to stand for 30 min, and impurities are removed by filtration to obtain a pure ferrous sulfate solution, and then a potentiometric titrator is used to determine the Fe content in the solution. 2+content, and continue to add hydrogen peroxide to the solution until it is completely oxidized to Fe 3+ , and finally a 0.8 mol / L ferric sulfate solution was obtained.
[0049] Example 1
[0050] This embodiment provides a method for preparing quasi-spherical iron phosphate.
[0051] (1) adding an appropriate amount of phosphoric acid to a ferric sulfate solution, controlling the molar ratio of Fe element to P element to be 1:0.55, and adding 0.04 wt % of sodium dodecylbenzene sulfonate (relative to the total mass of sodium dodecylbenzene sulfonate, phosphoric acid, ferric sulfate and water) thereto, stirring the mixture uniformly at a speed of 20 r / min on a magnetic stirrer, and then transferring the mixture into a high-pressure reactor for hydrothermal reaction at 150° C. for 1.5 h to obtain a mixed solution A;
[0052] (2) After the reaction in step (1) is completed, ammonium dihydrogen phosphate in an amount equimolar to phosphoric acid is added to the mixed solution A, and the hydrothermal reaction is continued for 1 hour to obtain a mixed solution B. After standing at room temperature for 25 minutes, the mixed solution B is washed with deionized water and filtered four times to retain the filter cake;
[0053] (3) The filter cake obtained in step (2) is mixed with deionized water to form a slurry, and the slurry is pumped into a spray drying furnace at a feed rate of 5 L / h, an inlet temperature of 240°C, and an outlet temperature of 115°C. The light yellow powder obtained by spray drying is then collected by a cyclone, sieved, and transferred to a high-temperature kiln. Compressed air is introduced and sintered at a temperature of 500°C for 1.5h. The high-temperature kiln heating rate is 5°C / min to obtain a spherical anhydrous iron phosphate material.
[0054] Figure 1 and Figure 2 This is a scanning electron microscope image of the spherical anhydrous iron phosphate material prepared in this example. Figure 3 This is a particle size distribution diagram of the quasi-spherical anhydrous ferric phosphate material prepared in this example. It can be seen from the figure that the obtained ferric phosphate material has a quasi-spherical aggregation morphology, no excessive agglomeration and a narrow particle size distribution.
[0055] Example 2
[0056] The difference between this embodiment and embodiment 1 is that in step (1), the molar ratio of Fe element to P element is controlled to be 1:0.6.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is that in step (1), the molar ratio of Fe element to P element is controlled to be 1:0.52.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 1 is that in step (2), sodium dodecylbenzene sulfonate is replaced by sodium dioctyl succinate sulfonate.
[0061] Comparative Example 1
[0062] This comparative example adopts sodium method coprecipitation process to prepare ferric phosphate. The specific steps are as follows:
[0063] An appropriate amount of phosphoric acid is added to the ferric sulfate solution, the molar ratio of the Fe element to the P element is controlled to be 1:1.3, and the solution is stirred evenly at a speed of 20 r / min on a magnetic stirrer to convert it into an iron phosphate solution with a pH of 1.8-2, and liquid alkali (30wt% sodium hydroxide solution) is added to precipitate the iron phosphate, and the iron phosphate precipitate is obtained after high-temperature aging at 85°C. After standing and stratification, the precipitate is filtered while hot, and the obtained filter residue is the product iron phosphate. After drying in an oven at 100°C, the product of white yellowish powdery dihydrate iron phosphate is obtained by grinding; the dihydrate iron phosphate is placed in a quartz boat and calcined at 500°C in an air atmosphere for 3 hours to obtain an anhydrous iron phosphate material.
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 1 is that this comparative example only undergoes one high-temperature liquid phase reaction, and the phosphorus source is only phosphoric acid. The specific steps are as follows:
[0066] (1) adding an appropriate amount of phosphoric acid to a ferric sulfate solution, controlling the molar ratio of Fe element to P element to be 1:1.1, and adding 0.04 wt % of sodium dodecylbenzene sulfonate (relative to the total mass of sodium dodecylbenzene sulfonate, phosphoric acid, ferric sulfate and water) thereto, stirring the mixture uniformly at a speed of 20 r / min on a magnetic stirrer, and then transferring the mixture into a high-pressure reactor for hydrothermal reaction at 150° C. for 2.5 h to obtain a mixed solution A; washing the mixed solution A with deionized water and filtering it four times, retaining the filter cake;
[0067] (3) The filter cake obtained in step (2) is mixed with deionized water to form a slurry, and the slurry is pumped into a spray drying furnace at a feed rate of 5 L / h, an inlet temperature of 240°C, and an outlet temperature of 115°C. The light yellow powder obtained by spray drying is then collected by a cyclone, sieved, and transferred to a high-temperature kiln. Compressed air is introduced and sintered at a temperature of 500°C for 1.5h. The high-temperature kiln heating rate is 5°C / min to obtain anhydrous iron phosphate material.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that this comparative example does not include a spray drying step. Step (3) of this comparative example is as follows:
[0070] (3) The filter cake obtained in step (2) is dried in an oven at 100° C. and then ground to obtain a white yellowish powdery ferric phosphate dihydrate product. The dried ferric phosphate dihydrate powder is then transferred to a high-temperature kiln, introduced with compressed air, and sintered at 500° C. for 1.5 h. The high-temperature kiln heating rate is 5° C. / min to obtain anhydrous ferric phosphate material.
[0071] Comparative Example 4
[0072] The difference between this comparative example and Example 1 is that diammonium phosphate and phosphoric acid are added at the same time. The specific steps are as follows:
[0073] (1) adding an appropriate amount of phosphoric acid and diammonium phosphate to a ferric sulfate solution, controlling the molar ratio of Fe element to P element to be 1:1.1, and the molar ratio of phosphoric acid to diammonium phosphate to be 1:1; adding 0.04 wt % of sodium dodecylbenzene sulfonate (relative to the total mass of sodium dodecylbenzene sulfonate, phosphoric acid, ferrous sulfate and water) thereto, stirring the mixture uniformly at a speed of 20 r / min on a magnetic stirrer, and then transferring the mixture into a high-pressure reactor to perform a hydrothermal reaction at 150° C. for 1.5 h to obtain a mixed solution A; standing at room temperature for 25 min, washing the mixed solution A with deionized water and filtering it four times, and retaining the filter cake;
[0074] (2) The filter cake obtained in step (1) is mixed with deionized water to form a slurry, and the slurry is pumped into a spray drying furnace at a feed rate of 5 L / h, an inlet temperature of 240°C, and an outlet temperature of 115°C. The light yellow powder obtained by spray drying is then collected by a cyclone, sieved, and transferred to a high-temperature kiln. Compressed air is introduced and sintered at a temperature of 500°C for 1.5 hours. The high-temperature kiln heating rate is 5°C / min to obtain anhydrous iron phosphate material.
[0075] Test example
[0076] 1. Preparation of lithium iron phosphate positive electrode material:
[0077] The iron phosphate prepared in Examples 1 to 4 or Comparative Examples 1 to 4 was mixed with lithium carbonate, glucose and PEG4000 to prepare a slurry and grinded uniformly to obtain a precursor slurry, wherein the molar ratio of iron phosphate to lithium carbonate was 1.05:0.5, the mass fraction of glucose in the whole powder was 9wt%, and the mass fraction of PEG4000 in the whole powder was 2wt%. After spray drying and air flow pulverization, the mixture was transferred to a roller kiln and sintered at 500°C for 5h in a nitrogen atmosphere, and then sintered at 640°C for 14h, and then demagnetized and sieved to obtain a lithium iron phosphate positive electrode material (LFP).
[0078] The properties of the iron phosphate and lithium iron phosphate materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were measured, and the test results are shown in Table 1.
[0079] Table 1 Performance measurement results of iron phosphate and lithium iron phosphate in the examples and comparative examples
[0080]
[0081] As can be seen from Table 1, compared with Comparative Example 1, the quasi-spherical iron phosphate prepared in Example has a higher specific surface area, and will have a higher reactivity when participating in the subsequent synthesis of lithium iron phosphate, so that the diffusion of the lithium source in the iron phosphate crystal phase is more uniform. On the basis of not losing the specific surface area, the embodiment also has a higher tap density, so that the subsequently synthesized lithium iron phosphate has a higher compaction performance than that synthesized in Comparative Example 1; the lithium iron phosphate powder prepared by the iron phosphate in Example has a lower resistance, which proves that the high reactivity of the precursor makes Li + The diffusion is more uniform, resulting in a higher purity of the lithium iron phosphate phase, so the powder resistance is reduced. At the same time, the iron phosphate in the embodiment is subjected to the process of thermal spraying and sintering, which makes it more crystalline and thus reduces the powder resistance of the prepared lithium iron phosphate.
[0082] Compared with Comparative Examples 2 and 4, the lithium iron phosphate in the embodiment has a larger specific surface area and a higher tap density due to the use of a two-stage high-pressure liquid phase method and two phosphorus sources with different functions, so that the subsequently prepared lithium iron phosphate has a higher compaction and a lower powder resistance. Compared with Comparative Example 3, the tap density of the iron phosphate in the embodiment is higher and the crystallinity is higher, so the prepared lithium iron phosphate powder has a lower resistance.
[0083] 2. Preparation of button cells: Add conductive carbon black to the N-methylpyrrolidone (NMP) solution of polyvinylidene fluoride (PVDF), then add the lithium iron phosphate positive electrode material (the mass ratio of lithium iron phosphate, PVDF and conductive carbon black is 90:5:5) prepared by using the iron phosphate as the precursor of the embodiment or the comparative example, stir evenly, and evenly apply the slurry on the aluminum foil on the coating machine to make the pole piece. Put the coated pole piece into a vacuum drying oven at a temperature of 120°C for vacuum drying for 6 hours, take out the pole piece and roll it on a roller press for standby use. The button cell assembly is carried out in a glove box under an argon atmosphere. The electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) containing 1M LiPF6 (the volume ratio of EC, DEC and DMC is 1:1:1), and the metal lithium sheet is the counter electrode. The capacity test was carried out on an American Arbin BT2000 battery tester. The charge and discharge voltage range was 2 to 3.75 V, and the charge and discharge rates were 0.1C, 0.5C, and 1C, respectively. The results are shown in Table 2.
[0084] Table 2 Electrical properties of button cells assembled with lithium iron phosphate prepared from examples and comparative examples
[0085]
[0086] Note: 3.1V&1C capacity ratio refers to the capacity when discharged at 1C rate to 3.1V.
[0087] Since the iron phosphate in the embodiment has higher reaction activity and crystallinity, the lithium iron phosphate prepared has higher specific capacity under various discharge rate states, and its comprehensive electrical properties are better than the lithium iron phosphate prepared in the comparative example.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing quasi-spherical iron phosphate, characterized in that: The steps include: S1, mixing ferric sulfate and phosphoric acid in water and performing a hydrothermal reaction; controlling the molar ratio of the iron element to the phosphorus element to be greater than 1; S2, after the reaction in step S1 is completed, adding ammonium dihydrogen phosphate so that the total molar amount of ammonium dihydrogen phosphate and phosphoric acid is not less than the molar amount of the iron element, and then performing a hydrothermal reaction; S3. After the reaction in step S2 is completed, washing, filtering, spray drying and sintering are performed in sequence to obtain quasi-spherical iron phosphate.
2. The preparation method according to claim 1, characterized in that In step S1, the molar ratio of iron element to phosphorus element is 1:(0.52-0.6); the molar ratio of diammonium phosphate in step S2 to phosphoric acid in step S1 is 1:(0.8-1.1).
3. The preparation method according to claim 1, characterized in that: The ferrous sulfate described in step S1 is obtained by oxidizing ferrous sulfate with an oxidant; the oxidant is selected from one or more of hydrogen peroxide, ozone, oxygen, sodium peroxide, potassium persulfate or ammonium persulfate.
4. The preparation method according to claim 3, characterized in that: The ferrous sulfate is obtained by removing impurities from ferrous sulfate, a byproduct of titanium dioxide, with an impurity remover; the impurity remover is selected from one or more of Na2S, (NH4)2S or BaS.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction of step S1 and step S2 is 140-200° C., and the reaction time is 1-5 hours.
6. The preparation method according to claim 1, characterized in that: The hydrothermal reaction in step S1 also contains a surfactant, and the added amount of the surfactant is 0.03-0.06 wt %.
7. The preparation method according to claim 6, characterized in that: The surfactant is selected from one or more of sodium dodecylbenzene sulfonate, dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate or sodium stearate.
8. The preparation method according to claim 1, characterized in that: The feed rate of the spray drying is 3-8 L / h, the inlet temperature is 220-250° C., and the outlet temperature is 110-120° C.; the sintering step of step S3 is specifically: heating to 450-550° C. at a heating rate of 3-8° C. / min, and sintering at this temperature for 2-6 hours.
9. The quasi-spherical iron phosphate prepared by the preparation method according to any one of claims 1 to 8.
10. The use of the quasi-spherical iron phosphate according to claim 9, characterized in that: The quasi-spherical iron phosphate is used to prepare lithium iron phosphate positive electrode material.
Citation Information
Patent Citations
Preparation method of high-rate lithium iron phosphate microsphere
CN111186827A
Iron phosphate precursor as well as preparation method and application thereof
CN113247876A
Preparation method of iron phosphate with high tap density, low sulfur and high iron-phosphorus ratio
CN115124012A
Iron phosphate as well as preparation method and application thereof
CN118324108A
Iron phosphate precursor and preparation method therefor and application thereof
WO2022227669A1
Cited By
Lithium iron phosphate positive electrode material, preparation method thereof and battery
CN121662811A
